2016
DOI: 10.1200/jco.2015.64.6729
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Surgical Procedure for Patients With Non–Small-Cell Lung Cancer ≤ 1 cm or > 1 to 2 cm Among Lobectomy, Segmentectomy, and Wedge Resection: A Population-Based Study

Abstract: Lobectomy showed better survival than sublobar resection for patients with NSCLC ≤ 1 cm and > 1 to 2 cm. For patients in whom lobectomy is unsuitable, segmentectomy should be recommended for NSCLC > 1 to 2 cm, whereas surgeons could rely on surgical skills and the patient profile to decide between segmentectomy and wedge resection for NSCLC ≤ 1 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
161
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(180 citation statements)
references
References 21 publications
6
161
1
1
Order By: Relevance
“…However, segmentectomy typically involves less lymph nodes (LN) dissection than lobectomy, which may explain the higher recurrence observed in patients treated by this method. Recently, a population study indicated that lobectomy harbored a better survival than segmentectomy in NSCLC patients with tumors measuring ≤1 cm or 1 to 2 cm (12). Although several studies have shown a better survival benefit of lobectomy, only few have investigated the impact of extent of lymph node removal on the long-term outcome.…”
Section: Introductionmentioning
confidence: 99%
“…However, segmentectomy typically involves less lymph nodes (LN) dissection than lobectomy, which may explain the higher recurrence observed in patients treated by this method. Recently, a population study indicated that lobectomy harbored a better survival than segmentectomy in NSCLC patients with tumors measuring ≤1 cm or 1 to 2 cm (12). Although several studies have shown a better survival benefit of lobectomy, only few have investigated the impact of extent of lymph node removal on the long-term outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective analysis of the results of limited resections compared to formal lobectomy in T1a NSCLC was performed by Dai et al (1). Based on their data, the authors concluded that lobectomy was superior to more limited resection for all tumors ≤2 cm.…”
mentioning
confidence: 99%
“…The reason for performing a uniportal segmentectomy for patients with an impaired lung function and/or a previous history of pulmonary resection or multiple pure GGO lesions with concurrent resection or a likelihood of having a second or even a third NSCLC resected in the future. However, in spite of controversy still remaining, most of them are good-risk suspected NSCLC patients with a diameter about 10 mm more or less or less proportion of solid component in our series (7,8). The preliminary data will be discussed in another recently submitted paper.…”
Section: Review Article On Thoracic Surgerymentioning
confidence: 78%
“…• Because most of these nodules, as you know, are present as more tiny, smaller, softer, deeper, invisible and impalpable, many VATS experts develop or design many different novel localization method (8,14), including but not limited to the following: ♦ Preoperative CT-guided hook-wire or microcoil or methylene blue staining; ♦ 3D CTA; ♦ Thoracoscopy exploration or in vivo finger palpation; ♦ DynaCT-guided (Hybrid OR); ♦ Mobile CT (O-arm); ♦ Intraoperative ultrasonography; ♦ Radio-guided localization; ♦ Magnetic navigational bronchoscopy.…”
Section: Spn Localizationmentioning
confidence: 99%